Environmental pollution and its impact on hypertension: a review - Che, Li; Wang, Zilong (Frontiers in Public Health, 2025)
This review aims to summarize the impact of environmental pollution on the development of hypertension. The processes of urbanization and industrialization have significantly increased various types of pollution in our surroundings. Research indicates that exposure to these pollutants can negatively affect cardiovascular function, which is a recognized risk factor for both the onset and progression of hypertension. In this review, we systematically summarize current findings, explore the relationship between environmental pollution and hypertension, discuss potential biological mechanisms underlying this association, and suggest directions for future research. Understanding these relationships is crucial for developing public health strategies aimed at preventing heart disease caused by pollution.